PENGEMBANGAN KATALIS BERBASIS NIMO ALUMINA UNTUK REAKSI HIDRODEOKSIGENASI MINYAK NABATI MENJADI BIOAVTUR - Dwiratna, Bralin; Soebagjo, Soebagjo (Jurnal Energi dan Lingkungan (Enerlink), 2015)
Catalysts NiMoP/?-Al O -B O have been successfully synthesized by impregnation method. The 2 3 2 3catalyst was developed to process of vegetable oil hydrodeoxygenation (HDO). The effect of theaddition of boron and phosphorus on the activity and selectivity was studied in this research . Inaddition , the determination of appropriate operating conditions were also studied in order to obtainproducts with good conversion and selectivity. The research was conducted on the preparation of thehydrodeoxygenation catalyst , test the activity and selectivity of hydrodeoxygenation catalysts, andcatalysts characterization using BET , XRD and AAS . To determine the performance of the catalyst ,the hydrodeoxygenation catalysts were tested their activity and selectivity which took place in a batchreactor at a pressure of 20-60 bar and a temperature of 320-360 ° C. The composition of products wereanalyzed by using a Gas Cromatography . From the implementation of HDO reaction of vegetable oilwith NiMoP( 0.6 % )/?- Al O - B O (1.7 %) catalyst, the value of conversion obtained was 81.45 % at 60 2 3 2 3o bar operating pressure conditions and temperature 360 C .Keywords: vegetable oil , hidrodeoksigenasi , catalyst Nimo - ?alumina